Identification of promising barley genotypes based on morphological genetic diversity - Kumar, Yogender; Sehrawat, Krishan Dutt; Singh, Jogendra; Shehrawat, Sachin (Journal of Cereal Research, 2021)
Estimation of genetic diversity in a crop species provides a basis for devising future strategies for their conservation and sustainable use in crop improvement. Genotypic variation in 72 barley genotypes was studied for ten morphological traits. Coefficient of variation attributed to genotypic diversity was recorded highest for grain yield (26.16%) followed by inclination angle (20.0%), internode length (13.11%) and tillers per meter (13.07%). However, days to maturity (2.69%) contributed less to diversity with lower coefficient of variation. The principal component analyses revealed that first four most informative components could explain about 71.0 % of total variation present in the studied genotypes. Hierarchical cluster analysis clubbed all the barley genotypes into eight clusters. Clusters III and V being the largest one with 14 genotypes each and with one genotype, cluster I was the smallest. Among all, maximum distance was displayed by clusters I and VI, however, highest diversity was exhibited by cluster V. The genotypes namely MGL 21 (early heading), MGL 38 (early maturing), MGL 47 (short plant height with high tillering), MGL 12 (high culm thickness), MGL 117 (long internodes), MGL 15 (long spikes), MBGSN 145 (high grain weight, high yield, lodging resistant) were identified as most diverse genotypes. Cluster I, IV and VII portrayed better performance for most of the traits studied. Genotypes from these groups could be utilized as donors in breeding programs for different agro-ecologies.